Sistem Pakar Berbasis Web Diagnosa Penyakit Burung Merpati Metode Naive Bayes - Prasetyo, Muhamad Yulianto; Darusalam, Ucuk; Benrahman, Benrahman (Politeknik Negeri Batam, 2020)
Pigeons are very close to human life, therefore doves are often pets or livestock. Caring for pigeons because of their uniqueness and care is not that difficult. Care that is not so difficult is not that doves are immune to chicks. Many people do not know how to treat pigeons with disease first. Therefore we need advice from experts on pigeons to treat the disease. Because the disease in pigeons can attack humans, it must be treated first. To overcome this problem, an expert system was built which was equipped with 10 diseases and 33 symptoms obtained from experts or experts. The Naive Bayes method is a simple classification method which results in a probability value for each disease that appears. This system is made with the advantages of a user friendly display on the gejela selection page. The final result of the diagnosis is according to the first treatment method before being taken to the vet, using a web-based system which can make it easier for users to get information for disease diagnosis in pigeons.